Control of Oocyte Reawakening by Kit. - Hatice Duygu Saatcioglu; Ileana Cuevas; Diego H Castrillon (PLoS Genetics)
In mammals, females are born with finite numbers of oocytes stockpiled as primordial follicles. Oocytes are "reawakened" via an ovarian-intrinsic process that initiates their growth. The forkhead transcription factor Foxo3 controls reawakening downstream of PI3K-AKT signaling. However, the identity of the presumptive upstream cell surface receptor controlling the PI3K-AKT-Foxo3 axis has been questioned. Here we show that the receptor tyrosine kinase Kit controls reawakening. Oocyte-specific expression of a novel constitutively-active KitD818V allele resulted in female sterility and ovarian failure due to global oocyte reawakening. To confirm this result, we engineered a novel loss-of-function allele, KitL. Kit inactivation within oocytes also led to premature ovarian failure, albeit via a contrasting phenotype. Despite normal initial complements of primordial follicles, oocytes remained dormant with arrested oocyte maturation. Foxo3 protein localization in the nucleus versus cytoplasm explained both mutant phenotypes. These genetic studies provide formal genetic proof that Kit controls oocyte reawakening, focusing future investigations into the causes of primary ovarian insufficiency and ovarian aging.